The use of soft technologies in the care of hypertensive patients in Family Health Strategy - Geanne Maria Costa Torres; Inês Dolores Teles Figueiredo; José Auricélio Bernardo Cândido; Ana Patrícia Pereira Morais; Maria Irismar de Almeida (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To analyze the use of soft technologies in the care of hypertensive patients in the Family Health Strategy. Method: Descriptive study with qualitative approach. A total of 14 hypertensives and 2 professionals from a Family Health team in a municipality in the interior of the state of Ceará, Brazil, participated in the study in 2016. Data were collected through a checklist for non-participant systematic observation, subsidized by a field diary, being treated by the Thematic Content Analysis. Results: The categories constructed were: Relational technologies in the care of the hypertensive in the FHS and communication process between health-hypertensive professional in the FHS. In care practices permeate soft technologies, relationships; soft-hard, technical knowledge; and hard, the material resources, and verbal communication predominates in interpersonal relationships, to the detriment of nonverbal signals. Conclusion: There is a need to strengthen communication skills and soft technologies to re-signify the production of health care.